Endometrial Tumor Microenvironment Alters Human NK Cell Recruitment, and Resident NK Cell Phenotype and Function - Degos, Clara; Heinemann, Mellie; Barrou, Julien; Boucherit, Nicolas; Lambaudie, Eric; Savina, Ariel; Gorvel, Laurent; Olive, Daniel (Frontiers in Immunology, 2019)
Endometrial Cancer is the most common cancer in the female genital tract in developed countries, and with its increasing incidence due to risk factors such as aging and obesity tends to become a public health issue. However, its immune environment has been less characterized than in other tumors such as breast cancers. NK cells are cytotoxic innate lymphoid cells that are considered as a major anti-tumoral effector cell type which function is drastically altered in tumors which participates to tumor progression. Here we characterize tumor NK cells both phenotypically and functionally in the tumor microenvironment of endometrial cancer. For that, we gathered endometrial tumors, tumor adjacent healthy tissue, blood from matching patients and healthy donor blood to perform comparative analysis of NK cells. First we found that NK cells were impoverished in the tumor infiltrate. We then compared the phenotype of NK cells in the tumor and found that tumor resident CD103+ NK cells exhibited more co-inhibitory molecules such as Tigit, and TIM-3 compared to recruited CD103- NK cells and that the expression of these molecules increased with the severity of the disease. We showed that both chemokines (CXCL12, IP-10 and CCL27) and cytokines profiles (IL-1β and IL-6) were altered in the tumor microenvironment and might reduce NK cell function and recruitment to the tumor site. This led to hypothesize that the tumor microenvironment reduces resident NK cells cytotoxicity which we confirmed by measuring cytotoxic effector production and degranulation. Taken together, our results show that the tumor microenvironment reshapes NK cell phenotype and function to promote tumor progression.